The Impact of External Shocks and Preferential Trade Arrangements on the Agricultural Gross Domestic Product of Peru, 1950-2007 - Tello, Mario D. (2010)
This paper examines the impact of external shocks and six preferential trade arrangements faced by the Peruvian economy during the period 1950-2007. The focus was the agricultural gross domestic product (GDP), its external and internal components, and the associated two sets of relative prices. The main results are on the one hand, that the per capita GDP shocks have affected the per capita agricultural GDP, its two components, and the associated price indices of the external agricultural GDP component. The impact on the prices of the agricultural GDP, particularly on the internal component, has been weaker. On the other hand, the set of six preferential arrangements has not affected the rate of growth of the per capita agricultural GDP and its internal GDP component in a statistically significant way. These arrangements affected, with different degrees of robustness, the agricultural GDP associated prices, particularly the external component.